STRATEGI MANAJEMEN PENDIDIKAN BERBASIS MUTU DALAM MENINGKATKAN KINERJA SEKOLAH DASAR IHSANIYAH 1 KOTA TEGAL - A. Istiawati; Beni Habibi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the quality-based education management strategy in improving the performance of SD Ihsaniyah 1 Tegal City. In the competitive era of globalization, educational institutions must transform into accountable and high-quality organizations. This study uses a qualitative approach with a descriptive research type. Data collection techniques include in-depth interviews, structured observation, and documentation studies. Data analysis follows the Miles, Huberman, and Saldana model, which includes data collection, data condensation, data presentation, and conclusion drawing. The focus of the research includes strategic planning, implementation of quality management (Total Quality Management), and the evaluation system (PDCA cycle) used to maintain organizational performance stability. The results of the study are expected to provide a conceptual model for managing quality-based primary schools that are adaptive to the challenges of the 21st century.